2022
DOI: 10.1098/rspb.2022.1458
|View full text |Cite
|
Sign up to set email alerts
|

First experimental evidence for active farming in ambrosia beetles and strong heredity of garden microbiomes

Abstract: Fungal cultivation is a defining feature for advanced agriculture in fungus-farming ants and termites. In a third supposedly fungus-farming group, wood-colonizing ambrosia beetles, an experimental proof for the effectiveness of beetle activity for selective promotion of their food fungi over others is lacking and farming has only been assumed based on observations of social and hygienic behaviours. Here, we experimentally removed mothers and their offspring from young nests of the fruit-tree pinhole borer, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…The ASVs identifying Wolbachia were excluded from further analyses, since insect related infection was not in the focus of our research on fungus garden material. It is worth mentioning, however, that Wolbachia has been present in several analyses of laboratory nests by now (this study and Nuotclà et al, 2021;Diehl et al, 2022), whereas material of field nests never contained Wolbachia.…”
Section: Laboratory Samples Data Preparationmentioning
confidence: 56%
“…The ASVs identifying Wolbachia were excluded from further analyses, since insect related infection was not in the focus of our research on fungus garden material. It is worth mentioning, however, that Wolbachia has been present in several analyses of laboratory nests by now (this study and Nuotclà et al, 2021;Diehl et al, 2022), whereas material of field nests never contained Wolbachia.…”
Section: Laboratory Samples Data Preparationmentioning
confidence: 56%
“…Bacteria and yeasts have been also isolated from X. germanus individuals or infested galleries, but their functions have not been determined (Hulcr et al, 2012;Agnello et al, 2017;Rassati et al, 2019). In some cases, bacteria found in association with ambrosia beetles have been considered as beneficial (Haanstad and Norris, 1985;Grubbs et al, 2011Grubbs et al, , 2020Barcoto et al, 2020;Diehl et al, 2022). Further studies are needed to characterize the specific ecological role of all these microorganisms for X. germanus.…”
Section: Discussionmentioning
confidence: 99%
“…Ambrosia beetles in the tribe Xyleborini (Scolytinae), which are an ecological clade within the bark beetles, tunnel into host trees for the purposes of cultivating their nutritional fungal mutualists (Hulcr and Stelinski, 2017;Diehl et al, 2022). The role(s) that MVOCs play within the fungus-farming ambrosia beetles is emerging, but could function as short-or long-range cues to indicate the suitability of host substrates for brood production (Hulcr et al, 2011;Kuhns et al, 2014;Egonyu and Torto, 2018;Kandasamy et al, 2019;Biedermann and Vega, 2020;Ranger et al, 2021a;Nones et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Whether all bark and ambrosia beetles are able to detect and react to fungal weeds is doubtful, but recent experiments on the ambrosia beetle, Xyleborinus saxesenii (Ratzeburg), revealed that this species can detect and selectively remove an Aspergillus fungal pathogen (Nuotclá et al 2019). Furthermore, beetles can actively promote their nutritional mutualists over fungal weeds (Diehl et al 2022). So far, it is unknown, however, how X. saxesenii and other farming beetles detect the presence of pathogens within nests.…”
Section: Introductionmentioning
confidence: 99%